WAYS TO IMPROVE STRATEGIC MANAGEMENT OF MANUFACTURING ENTERPRISES: A CASE STUDY OF UZBEKISTAN - Abdusalomov Marufjon Olimjon ugli (TADQIQOTLAR.UZ, 2024)
Abstract.  This paper explores the strategic  management challenges  faced  by manufacturing enterprises in Uzbekistan and proposes a framework for improvement. Uzbekistan's manufacturing sector is crucial for the country's economic development, yet  it  encounters  several  obstacles,  including  outdated  production  techniques, insufficient  skilled  labor,  and  a  lack  of  modern  management  practices.  This  study employs  the  IMRAD  (Introduction,  Methods,  Results,  and  Discussion)  structure  to analyze these issues and present actionable  recommendations. The findings suggest that  adopting  modern  strategic  management  frameworks,  enhancing  workforce training,  and  leveraging  technology  can  significantly  improve  the  effectiveness  of manuf